Indeks Kepuasan Mahasiswa terhadap Pelayanan Program Studi Pendidikan Matematika - Yoga Budi Bhakti; Eva Yuni Rahmawati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
This study aims to determine the level of satisfaction of mathematics education students to the service of the study program. This research is a qualitative descriptive research. Subjects in this study are active students of mathematics education courses semester academic year 2016/2017. Aspects reviewed to find out the satisfaction of the service of mathematics education program based on five dimensions of responsiveness, reliability, empathy, assurance, and tangibles. The results showed, in general of the five dimensions, the satisfaction of students of mathematics education to service study program in terms of five dimensions feel quite satisfied.